Water Tariffs and Consumers' Inaction - Carmine Ornaghi; Mirco Tonin (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study adoption by more than 150,000 households of an optional transitional water tariff implemented in the South-East of England in conjunction with an universal metering pro-gramme. We document how inertia leads customers to relinquish substantial financial gains, with less than a third of customers who would benefit from adopting the transitional tariff actually doing so. We also show how households responds not only to overall gains, but also to more short-term gains from adopting the tariff. Households in high income/high education neighbourhoods display a higher responsiveness to potential savings, as do households where the contract holder is of prime age instead of being more senior or junior. Finally, the probability of adoption is positively impacted by adoption by neighbours, thus suggesting the presence of peer effects. We also look at the timing of the call, showing how most customers choose to call early on, when less information is available, but the issue is more prominent. The choice of when to call is consistent with customers taking into account the option value of waiting, as well as future consumption patterns.
Keywords: D12; L95; Q25; 330; inertia; tariffs; water